Study on the Key Technology of Image Transmission Mechanism Based on Channel Coding Ghost Imaging - Leihong Zhang; Ye Hualong; Dawei Zhang (IEEE Photonics Journal)
Based on the analysis of the algorithm of ghost imaging and channel coding transmission, this paper combines the error detection and correction function of channel coding and accurate transmission of ghost imaging to complete image coding transmission. The mechanism of image transmission based on channel coding ghost imaging is studied. Compared with the traditional algorithm of ghost imaging, the mechanism of image coding and transmission greatly decreasing the error rate, reducing the storage space, enhancing the ability of anti-jamming and anti-interception, and realizing the accurate image coding transmission. It solves problems such as insufficient feasibility, low reduction degree, long imaging time of current imaging algorithm, and so on.